Perjuangan Tokoh dalam Novel “Ibu Ketika Surga itu Harus Pergi” Karya Utami Panca Dewi (Analisis Sosiologi Sastra) - Anastasia Ria Indrasworo; Masrin Masrin (Universitas Indraprasta PGRI, 2022)
The research objectives are 1) To describe the elements of the characters, characterizations, settings, and plots that shape the struggles of the characters in the novel